Compliance gaps and the failed promises of religious freedoms. Issue 1 (1st January 2019) - Mataic, Dane R.; Finke, Roger
ABSTRACT: Previous research has established the striking disconnect between states' constitutional promises of religious freedoms and their actual practices for supporting such freedoms. Yet, past research has not fully explained, measured, or tested the extent of why the disconnect occurs for protections of religious freedom. Using the Religion and State Collection (Round 3) and other country level data, we construct two measures for the discrepancy between constitutional promises of religious freedom and the level of restrictions placed on religions. Building on previous research and theory, we argue, that these discrepancies represent a compliance gap, and can be explained through social, economic, governance, and global dimensions. We conclude that although promises of religious freedom signal a commitment to protections, upholding these promises is reliant on the religious economy of the nation (e.g. social pressures) and the specific types of governance used (e.g. free elections and an independent judiciary). Despite the influence of global and economic factors in explanations of other compliance gaps, these were insignificant in understanding why religious freedom compliance gaps emerge.